THEORY AND PRACTICE OF PARTICIPATION IN BBC'S QUESTION TIME - Seridório, Daniele Ferreira; Rothberg, Danilo [UNESP] (Associacao Brasileira de Pesquisadores de Jornalismo, 2022)
Connections between public service broadcasters and viewers can take place in a variety of contexts, including TV programs where practices of interaction and participation seek to ensure the fulfillment of public media duties. Our research developed an analysis of BBC's Question Time, a television show first broadcast in 1979 and still on. Our goal was to investigate theoretical and empirical aspects of audience participation in the program. Our methods were document and program analysis, and interviews with BBC journalists. The results include a wide view of how Question Time and the participation it provides have evolved. We argue that participation in the media may be a way of reinforcing public service broadcasting commitments with the health of democracy.
Keywords: Media accountability; Participation; Public service broadcasting